Albert Eckstein: a pioneer in pediatrics in Turkey - Akar, Nejat (The Turkish Journal of Pediatrics, 2004)
A historical perspective is presented on Ord. Prof. Albert Eckstein, who was a pioneer of modern pediatrics in TUrkey. 2005 marks the 55th anniversary of Prof. Albert Eckstein's death and 60th anniversary of the establishment of the Pediatric Clinics of Ankara University, where he served as the founding director for five years.